A wall painting from the domus of Palazzo Govone-Caratti at Alba Pompeia (Italy) - Greta Acuto (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
The thesis project concerned the conservation of a roman fragmentary mural painting, found during the archaeological excavation held in the court of the medieval Palazzo Govone-Caratti at Alba in 2008. The aim of the project was the study of the items from a historical, artistic and scientific point of view with an interdisciplinary approach. The results of the study supported the restoration of the fragmented plasters focusing on the reconstruction of their original disposition.